A mesoporous metal–organic framework used to sustainably release copper(ii) into reducing aqueous media to promote the CuAAC click reaction. Issue 41 (22nd September 2022) - Hoffmann, Pascal; Lherbet, Christian; Fabing, Isabelle; Barthélémy, Marie-Claire; Borjon-Piron, Yann; Laurent, Christophe; Vigroux, Alain
Abstract : Cr-MIL-101-NH2 (MOF1 ) has been used to encapsulate large amounts of copper sulfate and the resulting loaded material, Cu@MOF1, was successfully used to promote the CuAAC click reaction. Abstract : The mesoporous metal–organic framework Cr-MIL-101-NH2 (MOF1 ) has been used to encapsulate, by a simple impregnation method, large amounts of copper sulfate. The resulting loaded material, Cu@MOF1, was successfully employed to slowly release copper(ii ) into an appropriate reaction medium in which the reducing agent sodium ascorbate reduces copper(ii ) to copper(i ), thus allowing the well-known copper(i )-catalyzed alkyne–azide cycloaddition (CuAAC) "click" reaction to proceed in the absence of potentially high local copper(i ) concentrations. The use of a MOF-based controlled copper release system such as Cu@MOF1 may be relevant for copper(i )-catalyzed reactions having substrates that could be degraded by potentially high local concentrations of copper(i ). The copper chelating ligand TBTA (tris(benzyltriazolylmethyl)amine), a very useful ligand for click chemistry, has been successfully attached to the pores of MOF1 . The resulting TBTA-functionalized MOF (MOF3 ) was compared with its non-functionalized version (MOF1 ). At copper loadings of ca. 3 mmol g −1, the results revealed that the performances of the two materials are strikingly similar. Upon immersion in methanol/water (95/5) containing sodium ascorbate, both materials slowly released copper encapsulated in their pores and could be recovered and reused efficiently for up to five reaction cycles without reloading with metal ion, while allowing the CuAAC reaction to proceed with excellent conversion rates and yields.